2007
DOI: 10.1161/circulationaha.106.683722
|View full text |Cite
|
Sign up to set email alerts
|

β2-Microglobulin as a Biomarker in Peripheral Arterial Disease

Abstract: Background-Peripheral arterial disease (PAD) is common but commonly unrecognized. Improved recognition of PAD is needed. We used high-throughput proteomic profiling to find PAD-associated biomarkers. Methods and Results-Plasma was collected from PAD patients (ankle brachial index of Ͻ0.90; nϭ45) and subjects with risk factors but without PAD (nϭ43). Plasma was analyzed with surface-enhanced laser desorption/ionization time-of-flight mass spectrometry to quantify 1619 protein peaks. The peak intensity of a 12-k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
96
2
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(102 citation statements)
references
References 38 publications
3
96
2
1
Order By: Relevance
“…18 In patients on HD, serum b 2 M is markedly increased and predicts all-cause mortality, 19,20 but studies on the relationship between serum b 2 M and cardiovascular disease are limited. It has been reported that serum b 2 M correlates with carotid IMT 21 and the number of calcified valves.…”
Section: Discussionmentioning
confidence: 99%
“…18 In patients on HD, serum b 2 M is markedly increased and predicts all-cause mortality, 19,20 but studies on the relationship between serum b 2 M and cardiovascular disease are limited. It has been reported that serum b 2 M correlates with carotid IMT 21 and the number of calcified valves.…”
Section: Discussionmentioning
confidence: 99%
“…29,[34][35][36][37][38][39][40][41] A full discussion of these nontraditional risk factors is beyond the scope of this review.…”
Section: Nontraditional Risk Factorsmentioning
confidence: 99%
“…6 The importance of a healthy endothelium is seen in cardiovascular and metabolic diseases, where endothelial dysfunction is associated with atherosclerosis, hypertension, and the metabolic syndrome. [7][8][9] Important in the development of such endothelial dysfunction are oxidative stress 10,11 and inflammation, 12,13 both of which are common in the pathogenesis of cardiovascular diseases.…”
mentioning
confidence: 99%